2013
DOI: 10.1111/epi.12481
|View full text |Cite
|
Sign up to set email alerts
|

Brief group psychoeducation for psychogenic nonepileptic seizures: A neurologist‐initiated program in an epilepsy center

Abstract: SUMMARYObjective: To evaluate therapeutic efficacy upon augmenting the initial communication to patients regarding the diagnosis of psychogenic nonepileptic seizures (PNES) with a novel, brief group psychoeducation administered by the same team that provided the video-electroencephalography (VEEG) confirmed diagnosis and within 4 weeks of the diagnosis. Methods: Prior to discharge from the epilepsy monitoring unit (EMU), a standardized communication strategy was utilized to explain the diagnosis of PNES to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 34 publications
0
59
0
4
Order By: Relevance
“…The scale assesses impairment in five areas of work and social activities, including work, home management, social leisure activities, private leisure activities, and family and relationships, with higher values indicating greater impairment. The WSAS has been established as a valid, reliable and sensitive measure in a number of different disorders, including depression, anxiety, OCD, phobic disorders, or insomnia and it has proven a sensitive measure in a number of studies of patients with psychogenic non-epileptic seizures [25][26][27][28][29].…”
Section: Work and Social Adjustment Scale (Wsas)mentioning
confidence: 99%
“…The scale assesses impairment in five areas of work and social activities, including work, home management, social leisure activities, private leisure activities, and family and relationships, with higher values indicating greater impairment. The WSAS has been established as a valid, reliable and sensitive measure in a number of different disorders, including depression, anxiety, OCD, phobic disorders, or insomnia and it has proven a sensitive measure in a number of studies of patients with psychogenic non-epileptic seizures [25][26][27][28][29].…”
Section: Work and Social Adjustment Scale (Wsas)mentioning
confidence: 99%
“…Improvements in HRQoL measures and the WSAS have previously been observed with brief psychoeducation [23,31] and with more intensive psychotherapy programmes for PNES [19] but not with the explanation of the diagnosis alone [12]. This suggests that more extensive psychological input than he explanation of the diagnosis alone or a short course of psychoeducation may be necessary to improve overall functioning and quality of life in patients with PNES.…”
Section: Well-being Outcomesmentioning
confidence: 93%
“…This suggests that the psychoeducation intervention is more effective in reducing seizure frequency than communication of the diagnosis on its own, which was previously only associated with the (short term) cessation of PNES in 16% of patients when the same communication strategy was used as in the current service evaluation [12]. Chen et al [31] previously evaluated a psychoeducation program for PNES which also showed that seizure frequency did not decrease in line with the intervention.…”
Section: Seizure Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Sin embargo, cuando esta explicación es aceptada puede tener consecuencias significativas en el futuro de las crisis y provocar mejorías. Chen et al (2013), llevaron a cabo un programa en el que, previo a la incorporación de los pacientes, se realizaba una explicación del diagnóstico de las CNEP utilizando una estrategia de comunicación estandarizada. En la misma se enfatizaba sobre los siguientes puntos: los ataques no son epilépticos; tienen una causa psicógena, lo cual no implica que las crisis sean causadas deliberadamente por el paciente; los conflictos internalizados o suprimidos son, la mayoría de las veces, las causas de los episodios; el objetivo de la intervención es lograr el control de los eventos y para ello se utiliza como instrumentos la aceptación y la responsabilidad.…”
Section: Enfoques Psicoeducativosunclassified